Elaboration of thoughts whilst translating text-based signs with graphic symbols: A study on reflection competences of pedagogical professionals in primary education sector - Susanne Schumacher; Ulrike Stadler-Altmann (Pensa MultiMedia, 2023)
In the context of teacher education, there should be various opportunities for pre or in-service teachers to expand their reflective competence as part of their pedagogical professionalism. The professionalisation of teachers for the primary education sector (Schumacher et al., 2020; Stadler-Altmann, 2018) is a central task in the higher education didactic learning environment of the EduSpace Lernwerkstatt [learning workshop] for both the Master's programme in Educational Science and for the sustainable exchange with pedagogical practice, e. g. through corresponding workshops. This contribution focuses on reflexively gained insights from teachers on the design and application of AAC according to the INbook model (Knoblauch, 2017). The data basis is the interviews with primary school teachers conducted after a series of workshops in the EduSpace Lernwerkstatt. The secondary analysis of the interview data is based on the competence categories of Baumert and Kunter (2006), the theory-based reflection definition of Wyss (2013, p. 5) and the multi-perspective reflection tool developed by Keller-Schneider (2020). Finally, it is proposed to mirror the development of professional knowledge with reflection competences for the teaching profession.